Dry Sliding Wear Behavior of Sn and NiSn Overlays on Cu Connectors - Sharma, Ashutosh; Ahn, Byungmin (Tribology Letters, 2018)
In this work, a systematic investigation of wear behavior of lead-free Sn and NiSn coatings under dry sliding conditions was studied. The Sn coatings were produced by electrodeposition method with varying current density from 0.1 to 0.5 Acm−2. For NiSn overlay, Sn coatings were deposited on pre-plated Ni on polished Cu foil substrates. The effects of current density, sliding distance, and load on friction coefficient (COF) and wear morphology were studied by employing ball-on-flat wear testing machine under dry sliding conditions. The tests were carried out under different loads from 5 to 25 N and for a sliding distance of 1800 m. The wear loss was evaluated in terms of track width and depth as well as mass loss of worn out tracks. The results show that the composition and microstructure of the electrodeposited overlays are related closely to the electrodeposition current density. The three-element CuNi(Sn) overlay exhibits a higher COF and excellent wear resistance as compared to Cu(Sn) overlay, the wear mechanism of plated overlays is also discussed and reported here.
Keywords: Adhesion; Ball-on-flat; Barrier films; Finishing; Nickel; Plating; Tin; Unlubricated friction